Diagnostic capabilities of breast scintigraphy and molecular imaging of the mammary glands in the detection of various biological subtypes of breast cancer - N. S. Popova; S. N. Novikov; P. I. Krzhivitskiy; L. A. Zhukova; P. V. Krivorotko; A. S. Artemyeva; A. E. Michnin; A. A. Valitova; V. V. Danilov; A. V. Chyornaya; T. T. Tabagua; Zh. V. Bryantseva; et al. (Опухоли женской репродуктивной системы, 2022)
Background. The accurate and early diagnosis of breast cancer can improve efficacy of the treatment. The standard diagnostic methods such as mammography, ultrasound, and magnetic resonance tomography have a pivotal role in the detection of breast tumors, however, in some cases, they have low diagnostic accuracy. Mammoscintigraphy (MSG) / molecular breast imaging (MBI) with tumor-specific radiopharmacy 99mTc-Technetril in patients with breast cancer can considerably increase the accuracy of diagnosis. However, the diagnostic performance of MSG / MBI in the detection of different biological subtypes of breast cancer is still under investigation.Aim. To evaluate the accuracy of MSG / MBI with 99mTc-Technetril in diagnosis of different biological subtypes of breast cancer.Materials and methods. The analysis included the results of MSG / MBI of 1080 patients (2154 mammary glands), who were examined for suspected breast cancer. MSG / MBI were performed 5–15 min after intravenous injection into the vein of one of the feet of 370–740 MBq of tumor-specific radiopharmacy 99mTc-Technetril. Examinations performed from 2007–2020 was carried out on the emission computed tomography Forte (Philips); since 2020 the molecular visualization has been providing on the special gamma-camera Discovery NM750b (General Electric). The obtained data were evaluated by 2 experienced radiologists. Verification of changes in breasts was provided by morphological examination (1060 cases) or dynamic observation.Results. The sensitivity, specificity and overall accuracy of MSG / MBI were 90 %, 98 %, 95 % correspondingly. When diagnosing tumors with a diameter of up to 10 mm, the sensitivity of MSG / MBI was decreased to 83 %. In patients with various biological subtypes, the sensitivity of MSG / MBI was as follows: luminal A – 88 %; luminal B– – 91 %; luminal B+ – 92 %; triple negative – 93 %; HER2-positive – 96 %. The intensity of tumor uptake depended on the biological subtype of breast cancer. The average values of the 99mTc-Technetril uptake coefficient were as follows: luminal A – 1.59; luminal B– – 1.71; luminal B+ – 1.95; triple negative – 1.93; HER2-positive – 2.22.Conclusion. Retrospective analysis indicate high diagnostic performance of MSG / MBI: sensitivity – 90 %, specificity – 98 %, accuracy – 95 %. There are significant differences in the intensity of 99mTc-Technetril accumulation in tumors in patients with different biological subtypes of breast cancer (p = 0.01–0.004). MSG / MBI characterized by significant differences in the sensitivity in the diagnosis of luminal A and HER2+ breast cancer subtypes: 88 % and 96 %, respectively (p = 0.02).